Impact of Intraoperative Findings on Hearing in Revision Ear Surgery - Andro Kosec; Josipa Zivko; Andro Kurtic; Mihael Ries; Dejan Tomljenovic; Jakov Ajduk (Iranian Journal of Otorhinolaryngology, 2023)
Introduction:Hearing results after chronic ear surgery encompass recurrence, localization and extent of cholesteatoma, type of surgery, ossiculoplasty methods, but rarely interpret intraoperative findings. This study aimed to analyze the impact of intraoperative findings in revision tympanomastoidectomy in predicting postoperative hearing.Materials and Methods:This was a retrospective non-randomized cohort of 101 patients treated for recurrent chronic otitis media by tympanomastoidectomy. The patients’ demographics, localizations of disease recurrence and perioperative hearing results were analyzed.Results:Logistic regression showed that presence of tympanic perforation (p=0.036), ossicular chain damage (p=0.006), were negatively associated with improved hearing postoperatively. Attic cholesteatoma was associated with better postoperative hearing (p=0.045). Presence of tympanic perforation (p=0.050), alongside perifacial localization of imflammation (p=0.021) and ossicle destruction (p=0.013) were associated with worse postoperative hearing results. Multivariate analysis confirmed that tympanic perforation (p=0.040, F=4.401), and ossicular chain involvement (p=0.025, F=5.249), were consistent negative predictors of hearing improvement, while postoperative deterioration of hearing was associated with tympanic perforation (p=0.038, F=4.465) and facial nerve dehiscence (p=0.045, F=4.160).Conclusions:Comparison of postoperative revision tympanomastoidectomy hearing outcomes revealed significant positive reductions in air-bone gap values, primarily at low and mid frequencies. Postoperative hearing results  at high frequencies are not affected by revision surgery.